2015
DOI: 10.1002/cncy.21624
|View full text |Cite
|
Sign up to set email alerts
|

Has Afirma gene expression classifier testing refined the indeterminate thyroid category in cytology?

Abstract: BACKGROUND: Thyroid fine-needle aspiration (FNA) plays a pivotal role in the evaluation of thyroid nodules. Up to 30% of cases are diagnosed as indeterminate by FNA, including atypia of undetermined significance, follicular lesion of undetermined significance, suspicious for a follicular neoplasm, and follicular neoplasm, with approximately two-thirds having a benign outcome. The gene expression classifier (GEC) test is a molecular test for cases with indeterminate cytology. The purpose of the current study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
77
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 21 publications
16
77
1
1
Order By: Relevance
“…Although Afirma's overall sensitivity and NPV in thyroid nodules with category III/IV cytology were both 100% due to the absence of false negative cases, its specificity and PPV were only 15 and 38%, respectively. These analytical performance characteristics are consistent with the observations of another study [19]. However, the fact that only 8 cases with a benign Afirma result were surgically confirmed limited the accuracy of the sensitivity, specificity and NPV of the Afirma GEC test obtained in the current study, the results of which should therefore be interpreted with caution.…”
Section: Discussionsupporting
confidence: 80%
“…Although Afirma's overall sensitivity and NPV in thyroid nodules with category III/IV cytology were both 100% due to the absence of false negative cases, its specificity and PPV were only 15 and 38%, respectively. These analytical performance characteristics are consistent with the observations of another study [19]. However, the fact that only 8 cases with a benign Afirma result were surgically confirmed limited the accuracy of the sensitivity, specificity and NPV of the Afirma GEC test obtained in the current study, the results of which should therefore be interpreted with caution.…”
Section: Discussionsupporting
confidence: 80%
“…Many studies have shown that genetic background is different between Asians and Western populations. For example, a gene expression classifier (Afirma) showed distinctly different sensitivity and specificity in different populations partly because of different genetic background [13, 20, 2225]. What is more, Xing M et al reported BRAF mutation occurred in about 45 % of PTC patients in the USA [26] while the rate reported in Asian was much higher, 63.7 % in the study from Jin L et al [27] and 58 % in the study from Lee JH [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our prevalence of malignancy was higher than outlined by the 2014 National SIAPEC-IAP guidelines [9] , The Bethesda System [7] (where the TIR-3A category is considered analogous to AUS/FLUS, and the TIR-3B category is considered analogous to FN/SFN), and the British Thyroid Association Royal College of Physicians guidelines [11] (in which the TIR-3A category corresponds to THY-3a, and TIR-3B category to THY-3f). This discrepancy is rather frequent in the international literature [25][26][27][28][29] , suggesting that TIR-3A and TIR-3B should be both considered as intermediate/high-risk categories. For this reason, a surgical approach should be considered for both categories rather than only for TIR-3B, as is recommended by the most important international guidelines [7,9,11] .…”
Section: Discussionmentioning
confidence: 82%